Potensi Pemanfaatan Atap Tribun Stadion Kapten I Wayan Dipta Gianyar sebagai PLTS Rooftop - Pradika, Gallant; Giriantari, Ida Ayu Dwi; Setiawan, I Nyoman (Majalah Ilmiah Teknologi Elektro; Vol 19 No 2 (2020): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2020.v19i02.P15, 2020)
Captain I Wayan Dipta stadium rooftop power plant is designed as an additional power supply to meet the stadium's electrical load needs. Roof plts design using 2 scenarios. Scenario 1 has a capacity of 83,300 Wp with a solar module of 238 units and a 2-unit inverter generating 112,321 kWh/year of energy and will supply the day load of transformers 2 and 3 stadiums of 35,470 kWh/year. Scenario 2 with a capacity of 156,800 Wp with a solar module of 448 units and 4 inverters generates 211,458 kWh/year of energy and will supply the day load of transformer 1 stadium at 100,919 kWh/year. Scenario 1 investment cost of Rp.1,178,760,000 with total income up to 25 years amounting to Rp.1,090,635,084 while in scenario 2 costs investment amounting to Rp.2,237,860,000 and income up to the 25th year amounting to Rp.3,126,761,273 in economic feasibility analysis using NPV, PI, and the DPP is only scenario 2 which can be said to be feasible because in the 25th year the income is greater than the investment, while in scenario 1 the income will be worth the same as the investment in the 29th year. This means the system in scenario 1 is not feasible because it has a DPP longer than the lifespan of the project.